Determination of the ciprofloxacin-resistant Escherichia coli isolated from chicken meat in Turkey - SAHIN, S. (Journal of the Hellenic Veterinary Medical Society, 2020)
In this study, the occurrence of the ciprofloxacin-resistant (CR) Escherichia coli in chicken meat was determined, and their clonal relations were investigated by using pulsed-field gel electrophoresis (PFGE). Antimicrobial resistance patterns of E. coli isolates were determined by using disc diffusion assay, and minimum inhibitory concentration of ciprofloxacin was determined by E-test. Plasmid-mediated quinolone resistance (PMQR) and extended spectrum beta-lactamase (ESBL) resistance genes were also screened through polymerase chain reactions. Sixty chicken meat samples were collected from different supermarkets and butchers in Sivas, Turkey. CR E. coli strains were determined in 59 (98.3%) chicken meat samples. By analyzing PFGE fingerprint data, 34 different pulsotypes were determined. All E. coli strains were found to be resistant to nalidixic acid, enrofloxacin, and norfloxacin. In addition, isolates were resistant to levofloxacin (40.7%), ampicillin (94.9%), trimethoprim-sulfamethoxazole (76.3%), tetracycline (69.5%), and chloramphenicol (44.1%). However, isolates were susceptible to imipenem and colistin. In this study, 81.4% of CR E. coli isolates were observed to have a multidrug-resistant profile, which is defined as resistance to three or more classes of antibiotics. Through phenotypic confirmation tests, five isolates (8.3%) were determined to be ESBL-producing. The PMQR genes were not determined in any of the isolates. Two isolates (3.4%) possessed the blaCTX-M and blaCMY-2 genes, and 40 isolates (67.8%) had the blaTEM gene. Taken together, retail raw chicken meat is highly contaminated with CR E. coli. However, these isolates are not found to be carriers of the PMQR genes, indicating a low public health problem.